Pelatihan Menulis Feature Bagi Siswa SMA Negeri 1 Bandar Baru Kabupaten Pidie Jaya - Nofiana S; Rahmi, Hayatun; Wardani, Vera; Alyani, Ainun (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Feature writing is a process of telling an event or topic in an in-depth and interesting way, by combining elements of fact, opinion, and a compelling storytelling style. Feature is different from news because it provides information that is more comprehensive, personalized, and evokes the reader's emotions. Feature contains “more” information than regular news, including things that may be overlooked by the news and may never be “stale” (not actual) like regular news. This training is conducted so that students can write features well. The method used in this community service is to use lectures, questions and answers, and group work by direct guidance. From the participants' good writing results, it can be concluded that students already understand feature writing well. Enthusiasm was also seen when students asked various things in the world of writing features and to the service team during the question and answer session. This is evident after they get the material and are guided and guided directly by lecturers and students so that in the end they are able to write features well that are diverse. With the training provided by the PKM Team, it shows that SMAN 1 Bandar Baru students have been able to write features with a variety of topics. The features writing training given to the students of SMAN 1 Bandar Baru went well.